PENGARUH KUALITAS TANGIBLE, RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPHATY DAN KOMPETENSI TENAGA PENJUALAN TERHADAP KEPUASAN PELANGGAN (AGENCY) PT RAJAWALI CITRA TELEVISI INDONESIA - Ajat Sudrajat; Murniyati Murniyati (Yayasan Akrab Pekanbaru, 2018)
This research is intended to know the influence of quality tangibles, reliability, responsiveness, assurance, and empathy and sales person competence either partially or simultaneously to the consumers' satisfaction and to know the more dominant at PT. RCTI. The theory used in this research is marketing management theory related to the service quality. It uses descriptive quantitative and case study using survey. This is also explanatory. The technique of data collection is interview, distributing the questionnary to the sample for 42 respondents and documentation study. To test the hyphotesis, it uses multiple regression by using t-test and F-test and the variable which significantly has a dominant influence on the reliability. With the value of determination coefficient (R Square) 64,4%, it means that the independent variable may describe the dependent variable, while the remaining 35,6% is explained by the other independent variables which are not included in the this study model. Key words: Tangibles, Reliability, responsiveness, Assurance, Empathy salesperson competencce Satisfaction of consumer.